The Representation of Youtubers and Instagrammers In International Audiovisual Production - Berlanga-Fernández, Inmaculada (2022)
The article analyses the inclusion of YouTubers and Instagrammers in international audiovisual production. It shows the progressive introduction of these figures in popular consciousness through the cultural map drawn by current film productions. A quantitative and qualitative content analysis was carried out on 1738 audiovisual productions that included the terms YouTuber or Instagrammer in the title or as a keyword. We accessed all the stories with these figures as subjects through IMDb to find out the number of productions, the progressive growth and the different audiovisual genres which portray them. Through an analysis of keywords, synopses and specialized reviews, it has been possible to determine the features of these new communicators as reflected by fiction films. The results show the weight of the negative characteristics in their personalities and performances, the absence of values and the risks derived from irresponsible use of the networks. Due to the capacity of cinema to question and educate, the conclusion is the need for ethical and aesthetic training by filmmakers and citizens consuming audiovisual media.